Proposing a conceptual framework of spiritual care competence for Chinese nurses. (23rd March 2020) - Cao, Yuling; Kunaviktikul, Wipada; Petrini, Marcia; Sripusanapan, Acharaporn
Abstract: Spiritual care competence of nurses is crucial to satisfy the spiritual needs of the clients, but the dearth of conceptual frameworks has hindered the clarification of the construct, especially for nurses in the People's Republic of China. This article developed a 3*3*3 matrix framework to clarify the components of spiritual care competence for Chinese nurses through the synthesis of existing empirical and theoretical work, which includes three aspects (awareness, understanding, and application) on three levels (intrapersonal, interpersonal, and transpersonal) of three contents of spirituality (namely, worldview, connectedness, and transcendence). The proposed framework can be used as a model to promote spiritual care competence of nurses in China. Adoption of the framework to guide studies would allow for the design of interventions for the attainment of this competence.